Effect Type Fixator on Batik with Natural Dyes of Green Betel Leaves (Piper Betle L) - Kristiana, Dewi; Fatimah, Siti; Haerudin, Agus (Prosiding University Research Colloquium, 2022)
Plants are one of the natural resources that can be used as natural textile dyes in Indonesia. Natural dyes in the textile industry, especially batik, can be used as an alternative to synthetic dyes to reduce the danger of waste generated from the production process. Green betel leaf can be used as a natural dye because it contains anthocyanin compounds. This study aims to see the different colors and color quality of green betel leaf extract. The method used is an experiment by creating a variety of fixative substances alum, lime and tunjung. The results showed that green betel leaf extract could be used for dyeing batik fabrics by the results of the L*, a*, b* color difference test and identification of color codes and color light through encycolorpedia. The color produced from green betel leaf extract at batik cloth with alum and lime fixator is Medium-light orange tunjung fixator orange. The results of the fastness test value for washing soap are on average 4 (good), and on dry rubbing, the average value is 4-5 (good), the oldest color is produced from the variation of the tunjung fixator. The interpretation of the fixator did not significantly affect the color produced and the color fastness to soap washing and dry rubbing.